A nova política nacional de desenvolvimento regional: uma análise sobre as estratégias de desenvolvimento territorial para o Brasil - Toppan, Ricardo Nagliati [UNESP] (2015)
Questions about regional inequalities are on the agenda of public policies at least for over sixty years in Brazil, covering different political-economic scenarios, national and global, and guided until the 1980s by structuralist thought whose focus has always been to overcome underdevelopment. The Globalization and the State decentralization brought new elements to the dynamic political and economic regions of the country, which after a considerable period without a regional policy nationwide, found himself again willing to face and break with the intrinsic regional inequalities to the territory Brazilian. With regard to discussions of regional development theories, especially those that proposed a territorial way, new mechanisms for political organization and instruments to boost the specific features of territories become increasingly present in the context of public policy. In this context, the Federal Government, through the Ministry of Integration, proposed in 2013 a national debate on the new challenges of the Brazilian regional issue, resulting in the New National Policy for Regional Development (PNDR), which will be the subject matter of this work. Thus, the objective of this dissertation is to make an analysis of the policy, by claiming to affirm it as a key tool to regain federal solidarity and contribute to regional development in a context of globalization. The New PNDR achieved important advances, especially for its national, at the democratic process of construction, for its change in scale of operation, the incentives in territorial governance mechanism and social participation, corresponding positively to recent theories of territorial development. However, the discussion did not progress satisfactorily about financial instruments for regional policies nor about relevant topics of the current tax system, nor about the competition between the regions and of tax competition practices. However, the discussion did not progress...